PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PREZI TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS IV UPTD SDN 12 TANAH TINGGI - Maya Dwi Astri (Universitas Negeri Medan, 2021)
Abstract : The Effect of The Use of Prezi Learning Media on Students' Learning Interest in Learning IPA in Class IV UPTD SDN 12 Tanah Tinggi. This study aims to determine the effect of using Prezi learning media on students' interest in learning Natural Sciences (IPA) in class IV UPTD SDN 12 Tanah Tinggi. This type of research is a quasi-experimental research which has a research sample of 22 students in the control class and 23 students in the experimental class so that the total sample in this study is 45 students. The data obtained were analyzed by testing for normality, homogeneity, the similarity of two averages, and hypothesis testing using the independent sample t test. The results of this study indicate that the use of Prezi media has an effect on students' interest in learning science in class IV UPTD SDN 12 Tanah Tinggi. There are differences in students' interest in learning science in class IV UPTD SDN 12 Tanah Tinggi between classes that use Prezi media and those that do not use Prezi media. The use of prezi media can increase students' interest in learning science in class IV UPTD SDN 12 Tanah Tinggi, because with creative media such as prezi students will get new experiences in learning so that they become more enthusiastic and enthusiastic about following lessons. Keywords : Prezi media, interest in learning, natural science Abstrak : Pengaruh Penggunaan Media Pembelajaran Prezi terhadap Minat Belajar Siswa pada Pembelajaran IPA di Kelas IV UPTD SDN 12 Tanah Tinggi. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media pembelajaran prezi terhadap minat belajar siswa pada pembelajaran Ilmu Pengetahuan Alam (IPA) di kelas IV UPTD SDN 12 Tanah Tinggi. Jenis penelitian ini adalah penelitian quasi eksperimen yang memiliki sampel penelitian berjumlah 22 orang siswa kelas kontrol dan 23 orang siswa kelas eksperimen sehingga total sampel dalam penelitian ini adalah 45 orang siswa. Data yang diproleh dianalisis dengan uji normalitas, homogenitas, kesamaan dua rata-rata, dan uji hipotesis menggunakan independent sample t Test. Hasil penelitian ini menunjukkan bahwa penggunaan media prezi berpengaruh terhadap minat belajar siswa pada pembelajaran IPA di kelas IV UPTD SDN 12 Tanah Tinggi. Terdapat perbedaan minat belajar siswa pada pembelajaran IPA di kelas IV UPTD SDN 12 Tanah Tinggi antara kelas yang menggunakan media prezi dengan yang tidak menggunakan media prezi. Penggunaan media prezi mampu meningkatkan minat belajar siswa pada pembelajaran IPA di kelas IV UPTD SDN 12 Tanah Tinggi, karena dengan adanya media kreatif seperti prezi siswa akan mendapatkan pengalaman baru dalam belajar sehingga menjadi lebih antusias dan bersemangat mengikuti pelajaran. Kata kunci : Media prezi, minat belajar, ilmu pengetahuan alam